(untitled) (Legal journal - Research in Legal and Social Sciences, 2017)
By way of introduction, it is appropriate to make brief preliminary considerations that will lead to the crux of this article, in search of the active legitimacy of the Public Ministry against the nebulous inaction in terms of non-compliance with alternative measures. In the criminal field, our Criminal Procedure Code refers to precautionary measures such as those acts with an insurance and provisional purpose. This institute introduced in the criminal jurisdiction, has been in constant evolution since the times of the High Middle Ages, where there were inquisitorial codes by absolute monarchies; an evolution that triggered an accusatory system like the one we have today. In our criminal ritual model, the institute of precautionary measures foreshadows that “...the rule composes freedom during the process and the absolute disqualification of all coercive measures of an afflictive nature and the obligation to provide incriminating elements against oneself.. .”. According to the jurist Adolfo Alvaro Velloso, in Argentina, one of the issues that presents the greatest conflict in the procedural field of the Republic is that related to procedural injunctions. Our Criminal Procedure Code, in its article 235 strictly discriminates the nature of the precautionary measures. When breaking down the same article, we highlight that “...the precautionary measure of a personal nature, which consists of arrest, preventive detention and preventive detention; and that of a real nature will be those provided for in the Civil Procedure Code. These may be imposed only in the cases expressly indicated by this Code and in special laws.”